Blood-spinal cord barrier alterations in a mouse model of centrifugation-induced hypergravity - Dubayle, David; Morel, Jean-Luc; Lemarchant, Sighild (Frontiers in Physiology, 2025)
Astronauts endure repetitive episodes of hypergravity (HG) during takeoff and landing of spaceflights, and also in space due to microgravity. Blood-brain barrier alterations and disruptions were recently reported in mice subjected to a short period of HG induced by centrifugation. In this study, we have evaluated if the blood-spinal cord barrier (BSCB) was also damaged by centrifugation-induced HG in mice. For that purpose, adult C57Bl/6J male mice were subjected to HG in a centrifuge at 2 g for 24 h, while control mice stayed in normogravity (n = 7-8 per group). Mice were sacrificed after centrifugation, and thoracic spinal cords collected for immunohistochemistry. Alterations of the BSCB were evaluated by measuring the immunoreactive areas of tight junction-associated proteins (claudin-5, occludin and zonula occludens-1 (ZO-1)) normalized to that of collagen IV-positive vessels. Additionally, the extravasation of a large blood-derived protein, fibrinogen, was quantified to determine if BSCB integrity was strongly impaired. Interestingly, a significant decrease in occludin level was measured in the spinal cord of HG 2 g mice compared to that of control 1 g mice (−28.6%, p = 0.0378), whereas claudin-5 (−20.6%, p = 0.2030) and ZO-1 (−19.6%, p = 0.3048) levels were not significantly affected. The decrease in occludin tight junction proteins was not accompanied by an extravasation of fibrinogen into the spinal cord parenchyma (p > 0.05). Overall, this study reports for the first time structural alterations of the BSCB in the context of hypergravity.